Frequency and histopathological type of laryngeal tumours at the University Hospital of Kinshasa, Democratic Republic of the Congo - Kayembe Kabutakapua, Emile; Mpiana Junior , Sympho; Kalala Kabala , Hilaire; Kabongo Beya , Francois; Ntumba Malemka , Alain; Tshingamb Kamin, Yasmin; Sekele , Patrick; Nyembue Tshipukane, Dieudonné (Orapuh Journal, 2025)
IntroductionLaryngeal tumours are common and affect people of all ages.ObjectiveThis study aims to determine the frequency, clinical characteristics, and histopathological profile of laryngeal tumours at the University Hospital of Kinshasa, Democratic Republic of the CongoMethodsThis retrospective study was conducted over an 11-year period from 2013 to 2023. All patient records with clinical data and well-documented histological results of laryngeal tumours were included. Data were analysed using SPSS 27.0 software and presented as percentages, means, or medians.ResultsA total of 105 patients with laryngeal tumours were included, of whom 25.7% had benign tumours and 74.3% had malignancies. The mean age of patients was 55.9 ± 16.5 years, ranging from 5 to 79 years. Males predominated, accounting for approximately three-quarters of the cases. The median time to consultation was 12 months, with a range of 1 to 60 months. All patients with laryngeal tumours reported dysphonia. Dyspnoea was reported by 92.3% of patients with malignancies and 74.1% of those with benign tumours. About two-thirds of the malignant tumours and three-quarters of the benign tumours were located in the glottic area. The most common histological types were squamous cell carcinoma (89.7%) for malignancies and papilloma (85.2%) for benign tumours.ConclusionThese findings illustrate that laryngeal tumours are frequent in our setting. Increased awareness is needed to promote preventive measures against this condition.